Cordycepin and the entomopathogenic fungus Cordyceps militaris - Wellham, Peter A D (2022)
Cordyceps militaris is a widespread entomopathogenic fungus found in Europe, Asia, and North America, with a large number of insect hosts, predominantly lepidopteran larvae (caterpillars). This species is well known for its production of the nucleoside analogue cordycepin (3’-deoxyadenosine). Co-produced with its protector molecule pentostatin, cordycepin is a polyadenylation inhibitor, via its active modified form as cordycepin triphosphate. Pentostatin protects cordycepin from degradation to 3’-deoxyinosine by inhibition of the enzyme adenosine deaminase. It has been shown to have anti-inflammatory effects and hence has been the subject of much pharmacological research. Until recently, very little was known about the role of cordycepin in the ecology of the fungus, or why its production is favoured by natural selection. There are also gaps in the understanding of the process of infection of the host by the fungus, which is directly followed by sexual development and the formation of stromata bearing sexual fruiting bodies and spores (ascospores). Understanding these areas could have implications for biological control of insect pests. Indeed, the related species Beauveria bassiana and Metarhizium anisopliae have been used as bioinsecticides, precluding the use of harmful chemical insecticides.